Development of Android Based Practical Learning Media with VR Commando 3D on Handball Learning Materials - Bogy Restu Ilahi; Septian Raibowo; Yarmani; Fina Hiasa (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
This study aims to develop an Android-Based Practical Learning Media with VR Commando 3D in Handball Learning Materials to Improve Students' Critical Thinking. The Android-Based Practicum learning media with VR Commando 3D which was developed with the help of the VR Commando 3D application will be tested on odd semester students who take the Handball course, Physical Education Study Program, FKIP UNIB. This study will use the Research to the 4D (four-D) research and development model by collecting research data using a questionnaire based on the Likert scale. There are three questionnaires that will be distributed in this study, namely a material expert questionnaire, a media expert validation questionnaire, and a user response questionnaire. The purpose of distributing the questionnaire was to determine the feasibility of developing Android-Based Handball media with VR Commando 3D that the researchers made. As a result, the total score obtained from the combined validation of material experts, media, and users is 139.5 or an average score of 4.1 which means that the Android-Based Handball Learning Media with VR Commando 3D that the researcher developed is in the feasible category. used in learning activities.